Graphene-based metal composite wave-absorbing material as well as preparation method and application thereof
Through the preparation method of impregnation-freeze-drying-thermal annealing, the controllable synthesis of graphene-based metal composite wave absorbing materials is achieved, and the problem of inflexible electromagnetic wave absorption in the prior art is solved, and the versatility of the material and the controllability of physical parameters is achieved.
Patent Information
- Application Number
- CN202411935603.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to achieve effective absorption of electromagnetic waves of different frequencies and absorption intensities, and there are huge challenges in precisely controlling single-atom-carrier interactions on the atomic scale.
By using the preparation method of impregnation-freeze-drying-thermal annealing, the graphene-based metal composite absorbing material is formed by mixing urea, metal brine aqueous solution with graphene oxide, adding PVA aqueous solution, and then frozen and freeze-dried. This method can achieve controlled loading and uniform dispersion of different metal atoms.
The broadband and versatility of graphene-based metal composite absorbing materials are realized, and can be suitable for scenarios with different frequency points and absorbing intensity. The physical parameters of the materials are controllable, supporting the establishment of systematic interactions and quantitative correlations of physical parameters.
Smart Images

Figure CN119873805A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of absorbing materials, and in particular to a graphene-based metal composite absorbing material and a preparation method and application thereof. Background Art
[0002] The type, size and geometry of a material jointly determine its physical properties. Historically, the progress of materials science has been driven by the discovery of new materials and the modulation of their size and structure to achieve specific physical properties, so that the resulting materials meet the traditional application requirements in the fields of energy storage, catalysis, optoelectronics, biomedicine and sensors. However, the rapid development of high-frequency wireless communications and electronic information technology has promoted the transformation of modern materials to more diverse application requirements, including multifunctionality, miniaturization, intelligence and contextualization, which is completely different from the previous emphasis on the performance of materials. For example, highly integrated circuits containing numerous micron and nanoscale components require precise elimination of interference between high-frequency electromagnetic signals. However, given the differences in the operating frequencies and frequency bands of various electronic components, integrated circuit systems may require a wide array of materials with dozens or even hundreds of electromagnetic absorbers, using the single physical properties of each material to absorb electromagnetic waves of different intensities and frequency bands. This has prompted people to shift their needs from traditional reliance on a single broadband electromagnetic response material to controllable frequency-selective electromagnetic absorbers. In addition, the material functions required by modern times often span multiple disciplines, making traditional empirical-based material selection methods insufficient to cope with such complexity and diversity. To address these challenges, an effective method is needed to establish quantitative and qualitative connections between material parameters and properties, and to develop materials suitable for different needs through precise reverse engineering. The key lies in selecting suitable materials and tailoring their physical properties to achieve programmability from micro to macro scales. However, this process is affected by many factors and is difficult to implement in practice.
[0003] Metal single atoms successfully dispersed on supports can exhibit maximum atomic utilization and excellent reaction selectivity, demonstrating their great potential as catalysts, which is fundamentally attributed to the interaction between single atoms and supports, which substantially changes the electronic properties of metal single atoms and supports. Since the performance of electromagnetic absorbing materials in many advanced applications is intrinsically linked to their electrical properties, precise manipulation of single atom-support interactions has become a potential strategy to achieve controllable tuning of electrical properties. However, despite this promise, the mechanisms of single atom-support interactions at the atomic level remain poorly understood, and precise control of these interactions has not yet been achieved. This limitation stems from the huge challenges in visualizing single atom-support interactions at the atomic scale and systematically establishing quantitative correlations between such interactions and physical parameters. These challenges have severely hindered the rational design of functional single atom-support composites.
[0004] Patent publication number CN118744983A discloses a method for preparing a metal single atom doped graphene absorbing material, which uses graphene oxide as the main body, urea as the nitrogen source to provide coordination atoms, and a metal salt solution as the metal single atom precursor. The graphene oxide is mixed with urea and the metal salt solution, and after a freeze-drying process, the graphene material is prepared by heat treatment and reduction under an inert gas protective atmosphere. However, this method can only be used for doping iron atoms, and cannot guarantee the loading of other metal atoms on graphene. Summary of the invention
[0005] The purpose of the present invention is to provide a graphene-based metal composite absorbing material and its preparation method and application. The preparation method of impregnation-freeze drying-thermal annealing is adopted to obtain the controllable synthesis of metal atoms of different types and different contents based on the graphene substrate, which has broad universality.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing a graphene-based metal composite absorbing material, comprising the following steps:
[0008] S1, mixing urea, a metal salt aqueous solution and a graphene oxide (GO) suspension, and performing immersion and dispersion treatment until the solution is uniformly dispersed to obtain a first mixed solution;
[0009] S2, adding a polyvinyl alcohol (PVA) aqueous solution dropwise into the first mixed solution to obtain a second mixed solution;
[0010] S3, freezing the second mixed solution at liquid nitrogen temperature, and then freeze-drying to obtain a brown composite powder;
[0011] S4, performing reductive annealing on the composite powder to obtain a graphene-based metal composite absorbing material.
[0012] Further, in step S1, the metal salt in the metal salt aqueous solution is one or more of chloride, nitrate, sulfate, acetate, and phosphate;
[0013] The metal elements in the metal salt include one or more of cobalt (Co), iron (Fe), nickel (Ni), zinc (Zn), copper (Cu), manganese (Mn), chromium (Cr), cadmium (Cd), titanium (Ti), gallium (Ga), lead (Pb), tin (Sn), antimony (Sb), silver (Ag), iridium (Ir), and ruthenium (Ru).
[0014] Further, in step S1, the concentration of the metal salt aqueous solution is 0.5 to 2 mmol / mL;
[0015] The concentration of the graphene oxide suspension is 1-5 mg / mL.
[0016] Furthermore, in step S1, the usage ratio of the urea, the metal salt in the metal salt aqueous solution and the GO in the GO suspension is 1 g: 0.36-4.8 mmol: 2.5-12.5 mg, and the loading amount of the metal atoms on the graphene substrate can be precisely controlled by changing the feed ratio.
[0017] Further, in step S1, the immersion time is 3 to 6 hours;
[0018] The dispersion treatment includes ultrasonic dispersion treatment and stirring dispersion treatment, and its purpose is to make the solution uniformly dispersed.
[0019] Furthermore, the ultrasonic dispersion treatment time is 0.1 to 12 hours, preferably 2 to 4 hours.
[0020] Furthermore, the stirring and dispersing process may be magnetic stirring or stirring with a stirring rod.
[0021] Further, in step S2, the concentration of the PVA aqueous solution is 10 to 20 mg / mL;
[0022] The mass ratio of PVA in the PVA aqueous solution to GO in the GO suspension is 1 to 4:1, the purpose of which is to maintain the stability and rheology of the solution interface system and to play a role in dispersing the loaded metal source.
[0023] Furthermore, in step S3, the quick freezing is to reduce the temperature of the second mixed solution to -25 to -15°C within 30 seconds; the freeze drying temperature is -55 to -45°C, the freeze drying time is 60 to 80 hours, the pressure is 0.1 to 1 kPa, and the freeze drying is carried out in a freeze dryer. During the quick freezing and freeze drying process, a mixture of urea and polyvinyl alcohol is used to form a uniform hydrogel with a cross-linked network. This method maintains a sufficient distance between each metal precursor molecule, ensuring that the spatially isolated metal precursors do not contact each other, thereby fixing them on the carrier and preventing agglomeration.
[0024] Furthermore, the quick freezing is carried out in a liquid nitrogen quick-freezing machine. Under normal pressure, the temperature of liquid nitrogen is generally -196°C. If pressurized, liquid nitrogen can be obtained at a higher temperature.
[0025] Furthermore, in step S4, the reduction sintering is annealed in nitrogen or inert atmosphere, the temperature is 500-600° C., the heating rate is 2-10° C. / min, and the holding time is 2-4 h.
[0026] Furthermore, the inert atmosphere includes argon and helium.
[0027] The second technical solution of the present invention is to provide a graphene-based metal composite absorbing material, which is prepared by the preparation method.
[0028] The third technical solution of the present invention is to provide a graphene-based metal composite absorbing material for use in the field of electromagnetic wave absorption.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] (1) The preparation method provided by the present invention can be applied to different metal atomic element compositions, has good universality, and can be efficiently applied to absorbing scenes with different frequencies and different absorbing intensities. Products with different absorbing properties can be obtained by different input amounts.
[0031] (2) The present invention mixes urea and metal salt aqueous solution with GO suspension in step S1, performs impregnation and dispersion treatment, and adds PVA aqueous solution in step S2, so that urea and PVA in the second mixed solution form a three-dimensional cross-linked network during the quick freezing and freeze-drying process. This method keeps a sufficient distance between each metal precursor molecule, ensures that the metal precursors isolated in space do not contact each other, so that they are fixed on the graphene substrate and prevent agglomeration, so that the metal precursor can be evenly loaded on the graphene substrate. Since the PVA aqueous solution has a certain viscosity, if it is added in advance, it is not conducive to further deep and uniform dispersion of metal ions.
[0032] (2) The present invention freezes the second mixed solution at liquid nitrogen temperature and then freeze-dries and freezes the second mixed solution in order to shape the second mixed solution when it is very evenly dispersed, which is beneficial for obtaining a precursor in which metal ions are evenly dispersed in graphene in the subsequent freeze-drying step. If normal freezing is performed instead of quick freezing, the solute in the solution will settle due to the long freezing time, destroying the even dispersion of metal ions in graphene.
[0033] (4) The present invention uses reductive annealing to allow metal atoms to freely diffuse on the substrate, and the single atoms synthesized by this method are evenly distributed and have good dispersion. The temperature of the reductive annealing is selected to be 500-600°C, because at 600-900°C, the metal ions are easily agglomerated to form clusters or nanoparticles due to the high temperature, while the temperature of 100-200°C is not enough to reduce the graphene oxide and anchor the metal ions on the graphene.
[0034] (5) The preparation method provided by the present invention does not introduce any harmful impurities during the entire preparation process, does not require extreme conditions, has a short reaction time, high reaction efficiency, low cost, low energy consumption, no waste generation, no pollution, and is economical and simple, with wide application potential.
[0035] (6) Each graphene-based metal composite absorbing material prepared by the present invention has different metal-substrate interactions when it meets different metals. For example, different metals have different strengths of coordination bonds with graphene, and this difference in interaction will affect the physical parameters of the material, such as polarization strength, resonance frequency, absorption strength, etc. Therefore, after preparing different metal single-atom loaded materials, by statistically analyzing their physical parameters, the relationship between this interaction and the physical parameters can be systematically established, and then a graphene-based metal single-atom composite absorbing material database can be obtained to guide material selection under different absorption requirements without tedious experiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is an X-ray diffraction pattern of the Co single-atom composite material with graphene as the substrate shown in Example 16;
[0037] Figure 2 This is a scanning electron microscope image of the graphene-based Co single-atom composite material shown in Example 16;
[0038] Figure 3 This is a spherical aberration-corrected transmission electron microscopy image of the Co single-atom composite material based on graphene shown in Example 16;
[0039] Figure 4 The real part (εˊ) of the dielectric constant of graphene-based metal composite absorbers with different types and contents of metal atoms: (a) Fe, (b) Co, (c) Zn, (d) Cu, (e) Mn, (f) Cr, (g) Cd, (h) Ti, (i) Ga, (j) Pb, (k) Sn, (l) Sb, (m) Ag, (n) Ir, (o) Ru;
[0040] Figure 5 The range of the polarization peak of the imaginary part of the dielectric constant (εˊˊ) of graphene-based metal composite absorbers with different types and contents of metal atoms: (a) Fe, (b) Co, (c) Zn, (d) Cu, (e) Mn, (f) Cr, (g) Cd, (h) Ti, (i) Ga, (j) Pb, (k) Sn, (l) Sb, (m) Ag, (n) Ir, (o) Ru;
[0041] Figure 6 A database of the absorption performance of graphene-based metal composite absorbing materials of different types and contents of metal atoms in the frequency range of 2 to 18 GHz;
[0042] Figure 7 The realization method of editable absorbing performance of graphene-based metal composite absorbing materials, (a) mode 1, (b) mode 2
[0043] Figure 8TEM image of the graphene-based metal composite material prepared in Comparative Example 2;
[0044] Fig. 9 TEM image of the graphene-based metal composite material prepared in Comparative Example 3;
[0045] Fig.10 This is a transmission electron microscope image of the graphene-based metal composite material prepared in Comparative Example 4;
[0046] Fig.11 is an X-ray diffraction pattern of the graphene-based metal composite material prepared in Comparative Example 5;
[0047] Fig.12 is an X-ray diffraction pattern of the graphene-based metal composite material prepared in Comparative Example 6;
[0048] Fig.13 This is a transmission electron microscope image of the graphene-based metal composite material prepared in Comparative Example 7. DETAILED DESCRIPTION
[0049] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0050] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.
[0051] In the following embodiments, the source of graphene oxide is graphene oxide dispersion 1-5 layers of Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., article number: 102145, CAS number: 7440-44-0, packaging: 100 mL, number: XF224, specification: 100 mL, concentration: 0.5 mg / ml; the source of polyvinyl alcohol is Sinopharm Chemical Reagent Co., Ltd., Sinopharm code C180301000, brand ACROS, specification Acros-180301000, 100 g.
[0052] A method for preparing a graphene-based metal composite absorbing material comprises the following steps:
[0053] S1, mixing urea, a metal salt aqueous solution and a GO suspension, and performing immersion and dispersion treatment until the solution is uniformly dispersed to obtain a first mixed solution;
[0054] S2, adding the PVA aqueous solution dropwise into the first mixed solution to obtain a second mixed solution;
[0055] S3, freezing the second mixed solution at liquid nitrogen temperature, and then freeze-drying to obtain a brown composite powder;
[0056] S4, performing reductive annealing on the composite powder to obtain a graphene-based metal composite absorbing material.
[0057] As one of the preferred embodiments, in step S1, the metal salt in the metal salt aqueous solution is one or more of chloride, nitrate, sulfate, acetate, and phosphate;
[0058] The metal elements in the metal salt include one or more of Co, Fe, Ni, Zn, Cu, Mn, Cr, Cd, Ti, Ga, Pb, Sn, Sb, Ag, Ir, and Ru.
[0059] As one of the preferred embodiments, in step S1, the concentration of the metal salt aqueous solution is 0.5 to 2 mmol / mL;
[0060] The concentration of the GO suspension is 1-5 mg / mL.
[0061] As one of the preferred implementations, in step S1, the usage ratio of the urea, the metal salt in the metal salt aqueous solution and the graphene oxide in the graphene oxide suspension is 1 g: 0.36-4.8 mmol: 2.5-12.5 mg, and the loading amount of metal atoms on the graphene substrate can be precisely controlled by changing the feed ratio.
[0062] As one of the preferred embodiments, in step S1, the immersion time is 3 to 6 hours;
[0063] The dispersion treatment includes ultrasonic dispersion treatment and stirring dispersion treatment, and its purpose is to make the solution uniformly dispersed.
[0064] As one of the preferred embodiments, the ultrasonic dispersion treatment time is 0.1 to 12 hours, preferably 2 to 4 hours.
[0065] As one of the preferred embodiments, the stirring and dispersing treatment may be magnetic stirring or stirring with a stirring rod.
[0066] As one of the preferred embodiments, in step S2, the concentration of the PVA aqueous solution is 10 to 20 mg / mL;
[0067] The mass ratio of PVA in the PVA aqueous solution to GO in the GO suspension is 1 to 4:1, the purpose of which is to maintain the stability and rheology of the solution interface system and to play a role in dispersing the loaded metal source.
[0068] As one of the preferred embodiments, in step S3, the quick freezing is to reduce the temperature of the second mixed liquid to -25 to -15°C within 30 seconds; the freeze-drying temperature is -55 to -45°C, the freeze-drying time is 60 to 80 hours, the pressure is 0.1 to 1 kPa, and the freeze-drying is carried out in a freeze dryer.
[0069] As one of the preferred embodiments, the quick freezing is carried out in a liquid nitrogen quick-freezing machine. Under normal pressure, the temperature of liquid nitrogen is generally -196°C. If pressurized, liquid nitrogen can be obtained at a higher temperature.
[0070] As one of the preferred implementations, in step S4, the reductive sintering is carried out under nitrogen or inert atmosphere, the temperature is 500-600° C., the heating rate is 2-10° C. / min, and the holding time is 2-4 h.
[0071] As one of the preferred implementations, the inert atmosphere includes argon and helium.
[0072] Examples 1 to 8
[0073] A method for preparing a graphene-based metal composite absorbing material (a Co single-atom composite material based on graphene), comprising the following steps:
[0074] S1, add 0.05g urea and Fe(NO3)3·9H2O aqueous solution (1mmol / mL) into 2.5mL GO suspension (specification 2mg / mL) after ultrasonic treatment for 3h, soak for 3h after mixing, and ultrasonic treatment for 3h to obtain the first mixed solution;
[0075] S2, adding 0.625 mL of PVA aqueous solution (16 mg / mL) dropwise into the first mixed solution to obtain a second mixed solution;
[0076] S3, freezing the second mixed liquid at liquid nitrogen temperature, freezing it to -20°C within 30s, and then freeze-drying it, the freeze-drying temperature is -50°C, the time is 72h, and the pressure is 0.5kPa, to obtain a brown composite powder. This method allows each metal precursor molecule to maintain a sufficient distance between each other, ensuring that the metal precursors isolated in space do not contact each other, so that they are fixed on the carrier and prevent agglomeration;
[0077] S4. Under the protection of argon atmosphere, the composite powder is reductively sintered at 550° C. for 3 h. After cooling to room temperature, a black-gray Co single-atom composite material based on graphene is obtained, namely, a graphene-based metal composite absorbing material. This step simultaneously realizes the reduction of GO, the doping of N elements and the loading of Co metal atoms on graphene.
[0078] In Examples 1 to 8, the addition amount of Fe(NO3)3·9H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Fe atoms on the graphene substrate is 0.5%, 1.0%, 1.2%, 1.4%, 1.8%, 2.6%, 2.9%, and 3.6%.
[0079] Embodiments 9 to 16
[0080] A method for preparing a graphene-based metal composite absorbing material (a Co single-atom composite material based on graphene), comprising the following steps:
[0081] S1, add 0.05g urea and Co(NO3)2·6H2O aqueous solution (1mmol / mL) into 2.5mL GO suspension (2mg / mL) after ultrasonic treatment for 3h, mix and soak for 3h, and ultrasonic treatment for 3h to obtain the first mixed solution;
[0082] S2, adding 0.625 mL of PVA aqueous solution (16 mg / mL) dropwise into the first mixed solution to obtain a second mixed solution;
[0083] S3, freezing the second mixed liquid at liquid nitrogen temperature, freezing it to -20°C within 30s, and then freeze-drying it, the freeze-drying temperature is -50°C, the time is 72h, and the pressure is 0.5kPa, to obtain a brown composite powder. This method allows each metal precursor molecule to maintain a sufficient distance between each other, ensuring that the metal precursors isolated in space do not contact each other, so that they are fixed on the carrier and prevent agglomeration;
[0084] S4. Under the protection of argon atmosphere, the composite powder is reductively sintered at 550° C. for 3 h. After cooling to room temperature, a black-gray Co single-atom composite material based on graphene is obtained, namely, a graphene-based metal composite absorbing material. This step simultaneously realizes the reduction of GO, the doping of N elements and the loading of Co metal atoms on graphene.
[0085] In Examples 9 to 16, the addition amount of Co(NO3)2·6H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Co atoms on the graphene substrate is 1.3%, 1.8%, 2.1%, 2.3%, 2.5%, 3.0%, 3.2%, and 3.4%.
[0086] Examples 17 to 24
[0087] A method for preparing a graphene-based metal composite absorbing material (Zn single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to a Zn(NO3)2·6H2O aqueous solution (1mmol / mL).
[0088] In Examples 17 to 24, the addition amount of Zn(NO3)2·6H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Zn atoms on the graphene substrate is 0.8%, 1.3%, 1.7%, 1.9%, 2.0%, 2.3%, 2.6%, and 2.9%.
[0089] Embodiments 25 to 32
[0090] A method for preparing a graphene-based metal composite absorbing material (Cu single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to a Cu(NO3)2·3H2O aqueous solution (1mmol / mL).
[0091] In Examples 25 to 32, the addition amount of Cu(NO3)2·3H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Cu atoms on the graphene substrate is 0.6%, 1.3%, 1.8%, 2.2%, 2.4%, 2.6%, 2.8%, and 3.0%.
[0092] Embodiments 33 to 40
[0093] A method for preparing a graphene-based metal composite absorbing material (Mn single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to a Mn(NO3)2·4H2O aqueous solution (1mmol / mL).
[0094] In Examples 33 to 40, the addition amount of Mn(NO3)2·4H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Mn atoms on the graphene substrate is 0.2%, 0.8%, 0.9%, 1.4%, 1.6%, 2.0%, 2.6%, and 2.8%.
[0095] Embodiments 41 to 48
[0096] A method for preparing a graphene-based metal composite absorbing material (a Cr single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to a Cr(NO3)3·9H2O aqueous solution (1mmol / mL).
[0097] In Examples 41 to 48, the addition amount of Cr(NO3)3·9H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Cr atoms on the graphene substrate is 1.2%, 1.4%, 1.7%, 2.2%, 2.5%, 2.6%, 2.8%, and 3.0%.
[0098] Embodiments 49 to 56
[0099] A method for preparing a graphene-based metal composite absorbing material (Cd single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to a Cd(NO3)2·4H2O aqueous solution (1mmol / mL).
[0100] In Examples 49 to 56, the addition amount of Cd(NO3)2·4H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Cd atoms on the graphene substrate is 0.8%, 1.1%, 1.4%, 2.1%, 2.5%, 2.7%, 3.1%, and 3.2%.
[0101] Examples 57 to 64
[0102] A method for preparing a graphene-based metal composite absorbing material (a Ti single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1 mmol / mL) is adjusted to a TiCl4 aqueous solution (1 mmol / mL).
[0103] In Examples 57 to 64, the amount of TiCl4 aqueous solution added is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Ti atoms on the graphene substrate is 0.7%, 1.8%, 2.4%, 2.5%, 2.8%, 3.1%, 3.4%, and 3.9%.
[0104] Embodiments 65 to 72
[0105] A method for preparing a graphene-based metal composite absorbing material (Ga single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to a Ga(NO3)3·5H2O aqueous solution (1mmol / mL).
[0106] In Examples 65 to 72, the addition amount of Ga(NO3)3·5H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Ga atoms on the graphene substrate is 0.8%, 1.4%, 2.0%, 2.5%, 3.1%, 3.2%, 3.7%, and 4.2%.
[0107] Embodiments 73 to 80
[0108] A method for preparing a graphene-based metal composite absorbing material (a Pb single-atom composite material based on graphene) is substantially the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1 mmol / mL) is adjusted to a Pb(NO3)2 aqueous solution (1 mmol / mL).
[0109] In Examples 73 to 80, the amount of Pb(NO3)2 aqueous solution added is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Pb atoms on the graphene substrate is 0.1%, 0.8%, 1.5%, 2.0%, 2.1%, 2.5%, 2.9%, and 3.4%.
[0110] Embodiments 81 to 88
[0111] A method for preparing a graphene-based metal composite absorbing material (Sn single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to a Sn(NO3)4 aqueous solution (1mmol / mL).
[0112] In Examples 81 to 88, the amount of Sn(NO3)4 aqueous solution added is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Sn atoms on the graphene substrate is 0.5%, 1.2%, 2.1%, 2.6%, 3.2%, 3.5%, 3.9%, and 4.1%.
[0113] Embodiments 89 to 96
[0114] A method for preparing a graphene-based metal composite absorbing material (Sb single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1 mmol / mL) is adjusted to a Sb(CH3COO)3 aqueous solution (1 mmol / mL).
[0115] In Examples 89 to 96, the amount of Sb(CH3COO)3 aqueous solution added is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Sb atoms on the graphene substrate is 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 3.0%, 3.5%, and 3.8%.
[0116] Examples 97 to 104
[0117] A method for preparing a graphene-based metal composite absorbing material (Ag single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1 mmol / mL) is adjusted to an AgNO3 aqueous solution (1 mmol / mL).
[0118] In Examples 97 to 104, the amount of AgNO3 aqueous solution added is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Ag atoms on the graphene substrate is 0.2%, 0.5%, 1.3%, 1.6%, 2.1%, 2.3%, 2.9%, and 3.7%.
[0119] Examples 105 to 112
[0120] A method for preparing a graphene-based metal composite absorbing material (Ir single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to an IrCl3·3H2O aqueous solution (1mmol / mL).
[0121] In Examples 105 to 112, the addition amount of IrCl3·3H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Ir atoms on the graphene substrate is 0.3%, 0.9%, 1.2%, 1.5%, 1.9%, 2.1%, 2.6%, and 3.8%.
[0122] Embodiments 113 to 120
[0123] A method for preparing a graphene-based metal composite absorbing material (Ru single-atom composite material based on graphene) is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to a RuCl3·3H2O aqueous solution (1mmol / mL).
[0124] In Examples 113 to 120, the addition amount of RuCl3·3H2O aqueous solution is set to 36, 48, 60, 72, 84, 96, 108, and 120 μL, respectively, so that the loading amount of Ru atoms on the graphene substrate is 0.6%, 1.0%, 1.2%, 1.5%, 1.9%, 2.0%, 2.2%, and 2.4%.
[0125] Embodiments 121 to 128
[0126] A method for preparing a graphene-based metal composite absorbing material (a Co, Fe diatomic composite material based on graphene), which is mostly the same as that of Examples 1 to 8, except that the Fe(NO3)3·9H2O aqueous solution (1mmol / mL) is adjusted to 120μL Co(NO3)2·6H2O aqueous solution (1mmol / mL) and 120μL Fe(NO3)3·9H2O aqueous solution (1mmol / mL), so that the loading amount of Co atoms on the graphene substrate is 1.3%, 1.8%, 2.1%, 2.3%, 2.5%, 3.0%, 3.2%, and 3.4%, and the loading amount of Fe atoms on the graphene substrate is 1.6%, 1.8%, 2.0%, 2.5%, 2.6%, 3.1%, 3.2%, and 3.6%.
[0127] Embodiment 129
[0128] A method for preparing a graphene-based metal composite absorbing material (Co atom composite material based on graphene) is mostly the same as that of Example 1, except that the concentration of the GO suspension is adjusted to 1 mg / mL.
[0129] Embodiment 130
[0130] A method for preparing a graphene-based metal composite absorbing material (Co atom composite material based on graphene) is mostly the same as that of Example 1, except that the concentration of the GO suspension is adjusted to 5 mg / mL.
[0131] Comparative Example 1
[0132] Compared with Example 8, most of the methods are the same, except that no Fe(NO3)3·9H2O aqueous solution is added to synthesize original pure graphene.
[0133] Comparative Example 2
[0134] Compared with Example 16, most of them are the same, except that the quick freezing and freeze drying in step S3 are changed to drying, the drying temperature is 70° C., and the drying time is 12 h.
[0135] Comparative Example 3
[0136] Compared with Example 16, most of the steps are the same except that no PVA aqueous solution is added.
[0137] Comparative Example 4
[0138] Compared with Example 16, most of the steps are the same except that the PVA aqueous solution is replaced with deionized water.
[0139] Comparative Example 5
[0140] Compared with Example 16, most of the steps are the same, except that the second mixed solution is directly freeze-dried without quick freezing.
[0141] Comparative Example 6
[0142] Compared with Example 16, most of the steps are the same, except that the temperature of the reduction sintering is adjusted to 800°C.
[0143] Comparative Example 7
[0144] Compared with Example 16, most of the steps are the same except that the temperature of the reduction sintering is adjusted to 200°C.
[0145] The graphene-based Co single-atom composite material prepared in Example 16 was analyzed using an X-ray diffractometer, and the obtained X-ray diffraction pattern is as follows: Figure 1 As shown (since the XRD spectra of the graphene-based metal composite absorbing materials prepared in other embodiments are basically similar to that in Example 1, they are not listed separately).
[0146] Figure 1 The X-ray diffraction peak of the graphene-based Co single-atom composite material shown in Example 16 only has the diffraction peak of graphene at a 2θ angle of about 20 degrees, and no other impurity peaks appear, which means that no Co crystals appear, proving that the Co element exists in a single atomic form.
[0147] The Co single-atom composite material with graphene as the substrate prepared in Example 16 was analyzed by scanning electron microscopy (SEM). Figure 2 ,The results show that there are no clusters or particles on the graphene surface, indicating that the Co metal element is distributed as a single atom on the substrate surface.
[0148] The graphene-based Co single-atom composite material prepared in Example 16 was characterized by spherical aberration-corrected electron microscopy. Figure 3 The white bright spot in the figure is single-atom Co. It can be seen that the Co element is distributed on the surface of the substrate in the form of single atoms, which is direct evidence of single atoms.
[0149] The inductively coupled plasma optical emission spectroscopy (ICP) test in Tables 1 and 2 shows the loading amount of Co atoms in Co single-atom composite materials with different graphene as substrates (Examples 9 to 16) and the loading amount of Co, Fe double single-atom composite materials with different graphene as substrates (Examples 121 to 128).
[0150] Table 1 Loading amount of Co single atom composite materials based on different graphene substrates
[0151]
[0152] Table 2 Loading amount of Co and Fe double single atom composite materials based on different graphene substrates
[0153]
[0154] The research on other types of single-atom materials based on graphene is basically the same as the above characterizations and results, so they are not listed here one by one.
[0155] According to another aspect of the present application, the application of the above-mentioned graphene-based metal composite absorbing material in the field of electromagnetic wave absorption is also provided. The single-atom composite has numerous polarization sites, which can be used to induce customized dipole polarization phenomena under microwave fields, and can be used as a future electromagnetic wave absorbing material with excellent performance.
[0156] Figure 4 , Figure 5 The range of the polarization peaks of the real part (ε′) and the imaginary part (ε″) of the complex dielectric constant of the graphene-based metal composite absorbing material is used to demonstrate the mechanism of its editable absorbing performance. The absorbing performance of the graphene-based metal composite absorbing material mainly comes from the dielectric loss capacity and magnetic loss. Since the material in the present invention is non-magnetic at room temperature, the complex magnetic permeability is not discussed. It can be found that the dielectric parameters of graphene-based metal composite absorbing materials of various types and different loading contents based on graphene change relatively slowly in the range of 2 to 18 GHz, indicating its higher dielectric performance. The imaginary part of the dielectric constant has a polarization loss peak, and the increment of the polarization loss peak gradually increases with the increase of the content.
[0157] Figure 6It is a database of the absorbing performance of various types and different loading contents of graphene-based metal composite absorbing materials based on graphene. It contains the absorption performance of various types and different loading contents of graphene-based metal composite absorbing materials based on graphene in the frequency range of 2 to 18 GHz. These ranges are divided into C (4 to 8 GHz), X (8 to 12 GHz), and Ku (8 to 12 GHz) bands, and different bands have different application scenarios. It was found that under the best matching thickness, different types of graphene-based metal composite absorbing materials have higher absorption rates at different frequencies, and as the content changes, the absorption rate of the same metal atoms at the same frequency point will change accordingly. The database is obtained by inputting the electromagnetic parameters of various types and different loading contents of graphene-based metal composite absorbing materials based on graphene, calculating the reflection loss (RL) through the formula, and converting the obtained absorption rate statistics. The specific formula for calculating the reflection loss (RL) is:
[0158]
[0159] Z in and Z o Represents input and air impedance. εr and μr are complex permittivity and complex permeability. f and c are frequency and speed of light. d is the matching thickness. The formula for conversion to absorptivity is:
[0160] Absorptionrate(%)=100×(1-10 RL / 10 ) (3)
[0161] Figure 7 The invention is a method for realizing the editable absorbing performance of various graphene-based metal composite absorbing materials with different types and different loading contents based on graphene. Specifically, it can be divided into two modes. The first mode: when the required absorption rate and working frequency are input (such as 95%, 10.2GHz), the database can recommend the optimal preparation parameters of graphene-based metal composite absorbing materials) (such as Co, 1.3%). The second mode: when the required absorption rate and a specific working range are input (such as >92%, 10.2-13.6GHz), the database can recommend the optimal preparation parameters of various graphene-based metal composite absorbing materials (such as Co / Fe, 1.3% / 3.6%).
[0162] Figure 8 This is a transmission electron microscope image of the graphene-based metal composite material prepared in Comparative Example 2. It can be seen that there are many nanoparticles, which means that the graphene-based metal composite absorbing material obtained in Comparative Example 2 has poor uniformity and a completely dispersed and uniform Co / graphene single atom composite material is not obtained.
[0163] Fig. 9This is a transmission electron microscope image of the graphene-based metal composite material prepared in Comparative Example 3. It can be seen that there are many nanoparticles, which means that the graphene-based metal composite absorbing material obtained in Comparative Example 3 has poor uniformity and a completely dispersed and uniform Co / graphene single atom composite material is not obtained.
[0164] Fig.10 This is a transmission electron microscope image of the graphene-based metal composite material prepared in Comparative Example 4. It can be seen that there are many nanoparticles, which means that the graphene-based metal composite absorbing material obtained in Comparative Example 4 has poor uniformity and a completely dispersed and uniform Co / graphene single atom composite material is not obtained.
[0165] Fig.11 This is the X-ray diffraction pattern of the graphene-based metal composite material prepared in Comparative Example 5. The diffraction peak of metal cobalt is very strong, and it can be seen that there are many nano-cobalt crystals, indicating that the graphene-based metal composite absorbing material obtained in Comparative Example 5 has poor uniformity, and a completely dispersed and uniform Co / graphene single atom composite material is not obtained.
[0166] Fig.12 This is the X-ray diffraction pattern of the graphene-based metal composite material prepared in Comparative Example 6. The diffraction peak of metal cobalt is very strong, and it can be seen that there are many nano-cobalt crystals, indicating that the graphene-based metal composite absorbing material obtained in Comparative Example 6 has poor uniformity, and a completely dispersed and uniform Co / graphene single atom composite material is not obtained.
[0167] Fig.13 This is the X-ray diffraction diagram of the graphene-based metal composite material prepared in Comparative Example 7. It can be seen that there are some nanoparticles because the metal salt has not been completely reduced at this sintering temperature, and the metal still exists in the form of agglomeration in the form of metal salt and has not been diffused and anchored into single atoms.
[0168] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a graphene-based metal composite absorbing material, characterized in that: The following steps are involved: S1, mixing urea, a metal salt aqueous solution and a graphene oxide suspension, and performing immersion and dispersion treatment until the solution is uniformly dispersed to obtain a first mixed solution; S2, adding the PVA aqueous solution dropwise into the first mixed solution to obtain a second mixed solution; S3, freezing the second mixed solution at liquid nitrogen temperature, and then freeze-drying to obtain a brown composite powder; S4, performing reductive annealing on the composite powder to obtain a graphene-based metal composite absorbing material.
2. The method for preparing a graphene-based metal composite absorbing material according to claim 1, characterized in that: In step S1, the metal salt in the metal salt aqueous solution is one or more of chloride, nitrate, sulfate, acetate, and phosphate; The metal elements in the metal salt include one or more of Co, Fe, Ni, Zn, Cu, Mn, Cr, Cd, Ti, Ga, Pb, Sn, Sb, Ag, Ir, and Ru.
3. The method for preparing a graphene-based metal composite absorbing material according to claim 1, characterized in that: In step S1, the concentration of the metal salt aqueous solution is 0.5 to 2 mmol / mL; The concentration of the graphene oxide suspension is 1-5 mg / mL.
4. The method for preparing a graphene-based metal composite absorbing material according to claim 1, characterized in that: In step S1, the ratio of the amount of urea, the metal salt in the metal salt aqueous solution and the amount of GO in the GO suspension is 1 g: 0.36-4.8 mmol: 2.5-12.5 mg.
5. The method for preparing a graphene-based metal composite absorbing material according to claim 1, characterized in that: In step S1, the immersion time is 3 to 6 hours; The dispersion treatment includes ultrasonic dispersion treatment and stirring dispersion treatment.
6. The method for preparing a graphene-based metal composite absorbing material according to claim 1, characterized in that: In step S2, the concentration of the PVA aqueous solution is 10 to 20 mg / mL; The mass ratio of PVA in the PVA aqueous solution to graphene oxide in the graphene oxide suspension is 1 to 4:
1.
7. The method for preparing a graphene-based metal composite absorbing material according to claim 1, characterized in that: In step S3, the quick freezing is to reduce the temperature of the second mixed solution to -25 to -15°C within 30 seconds; and the freeze-drying temperature is -55 to -45°C.
8. The method for preparing a graphene-based metal composite absorbing material according to claim 1, characterized in that: In step S4, the reduction sintering is carried out in nitrogen or an inert atmosphere at a temperature of 500-600°C.
9. A graphene-based metal composite absorbing material, prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the graphene-based metal composite absorbing material as claimed in claim 9 in the field of electromagnetic wave absorption.
Citation Information
Patent Citations
Preparation method of shape-controlled graphene / Co(OH)2 composite materials
CN105719849A
Graphene foam loaded nano Fe3O4 magnetic particle composite wave-absorbing material and preparation method thereof
CN107418513A
Preparation method of magnetic nanoparticle loaded graphene aerogel composite material
CN108439376A
Three-dimensional ordered porous graphene wave-absorbing material and preparation method thereof
CN113511648A
Method for efficiently growing carbon nanotubes
CN118183712A